Preparation and application method of asymmetric electromagnetic shielding nanofiber film
Through electrospinning technology and Joule heat treatment, an asymmetric electromagnetic shielding nanofiber film was prepared, which solved the problems of heavy, high cost and secondary pollution of existing electromagnetic shielding materials, achieved lightweight, efficient and multifunctional electromagnetic wave shielding performance, and had excellent resistance to extreme environments.
Patent Information
- Application Number
- CN202411903967.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing electromagnetic shielding materials have problems such as heavy, poor flexibility, high cost, and the strong reflection of incident electromagnetic waves by traditional uniform conductive systems, which lead to secondary pollution, making it difficult to meet the needs of modern electronic equipment for lightweight, high-efficiency, and multifunctional electromagnetic wave shielding materials.
The nanofiber substrate is constructed through electrospinning technology, combined with Joule thermal technology and Fick diffusion theory, and asymmetric structural design of conductive-dielectricity is achieved, and an asymmetric electromagnetic shielded nanofiber film is prepared. The method includes the steps of preparing SiO2 nanoparticles, forming PAN/SiO2 nanofiber films, pre-oxidation treatment, Joule heat treatment, etc., to form a multi-layer interface structure with a conductive-dielectric gradient.
It has achieved lightweight and efficient electromagnetic wave shielding performance, with excellent extreme temperature resistance and acid-base resistance. The stability of electromagnetic shielding performance is above 90%, and the stability after acid-base treatment is maintained at above 95%, which significantly shortens the production cycle and improves production efficiency.
Smart Images

Figure CN119711051A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic shielding and functional film preparation, and in particular to a preparation and application method of an asymmetric electromagnetic shielding nanofiber film. Background Art
[0002] With the rapid development of wireless communication technology and electronic devices, the problem of electromagnetic wave pollution has become increasingly serious, and higher requirements have been placed on efficient and lightweight electromagnetic shielding materials. At present, although traditional electromagnetic shielding materials (such as metal foils and carbon-based composite materials) have high shielding effectiveness, they generally have problems such as thickness, poor flexibility, and high cost. In recent years, lightweight, efficient, and stable electromagnetic shielding materials have gradually become a research hotspot. Improving adjustable multiple electromagnetic losses and achieving stable electromagnetic shielding performance are issues that urgently need to be solved.
[0003] The preparation of conductive materials with unique structures provides a main idea for optimizing the reflection and absorption of electromagnetic waves and the interface between the substrate. For example, porous structures, mesh structures, multilayer structures, honeycomb structures, sandwich structures, etc. are all methods to improve multiple losses. By introducing polarized charge layers and conductive networks at the interfaces of different components, the reflection and absorption of electromagnetic waves can be greatly enhanced. However, the strong reflection of incident electromagnetic waves by the uniform conductive system in the traditional shielding network leads to secondary pollution, which becomes a bottleneck restricting its application. The electromagnetic shielding film with asymmetric structure can achieve excellent electromagnetic wave shielding performance and lightweight design due to its unique interface effect and multifunctional characteristics. However, the current preparation technology for asymmetric electromagnetic shielding films still has problems such as high complexity and high cost, which is difficult to meet the needs of actual applications. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing an asymmetric electromagnetic shielding nanofiber film, constructing a nanofiber substrate through electrospinning technology, and combining Joule heating technology and Fick's diffusion theory to achieve a conductive-dielectric asymmetric structure design to meet the needs of modern electronic equipment for lightweight, high-efficiency and multifunctional electromagnetic wave shielding materials.
[0005] A method for preparing an asymmetric electromagnetic shielding nanofiber film of the present invention comprises the following steps:
[0006] (1) Preparing SiO2 nanoparticles as a silicon source; SiO2 nanoparticles are selected because of their good thermal and chemical stability. During the subsequent high-temperature treatment process, SiO2 can react with carbon to form silicon carbide (SiC), which is a material with high conductivity, high hardness and good corrosion resistance, and is very suitable for electromagnetic shielding;
[0007] (2) dissolving SiO2 nanoparticles in an organic solvent, stirring and ultrasonicating the solvent to obtain a SiO2 nanoparticle dispersion; then adding a high molecular weight polymer as a carbon source to the SiO2 nanoparticle dispersion, and uniformly stirring the solvent to obtain a spinning solution; this process not only allows the nanoparticles to be evenly distributed in the fiber, but also gives the material a larger specific surface area and porosity, which is beneficial to improving the electromagnetic wave absorption efficiency;
[0008] (3) The spinning solution is transferred into a syringe, and after adjusting the electrospinning parameters, the spinning solution is subjected to electrospinning operation to prepare a PAN / SiO2 nanofiber film; electrospinning can form a nanofiber network with a high specific surface area and a porous structure. This microstructure not only increases the interaction interface between the material and the electromagnetic wave, but also promotes multiple reflections and scattering inside, further enhancing the electromagnetic wave absorption capacity; in addition, the nanoscale fiber structure also gives the material excellent mechanical strength and flexibility;
[0009] (4) The PAN / SiO2 nanofiber film is pre-oxidized to carbonize the polymer to form a carbon-based skeleton, thereby obtaining a carbon-based film. The pre-oxidation treatment causes PAN (polyacrylonitrile) to undergo a chemical transformation, which ultimately carbonizes to form a stable carbon-based structure. This transformation enhances the mechanical strength and durability of the material, allowing the nanofiber film to maintain its integrity when facing external pressure or deformation.
[0010] (5) Using the Joule heat effect, SiO2 and the carbon-based film undergo a carbon thermal reaction to generate silicon carbide. Joule heat can be used to quickly initiate a reaction in a short time, so that silicon dioxide and the surface of the carbon-based film undergo a rapid carbon thermal reaction to generate SiC, significantly shortening the production cycle. Due to the existence of the Fick diffusion effect, the concentration gradient migration of SiO2 vapor is achieved under high temperature conditions. The content of SiC nanoparticles on the surface of the film is induced to change layer by layer through heat treatment, forming a multilayer interface structure of conductive-dielectric gradient. In addition, the conductive-dielectric gradient in the film optimizes the impedance matching of electromagnetic wave attenuation, which can achieve efficient electromagnetic interference shielding. At the same time, the asymmetric electromagnetic shielding nanofiber film after Joule heat treatment has stable structure and performance at higher temperatures. At the same time, it has good chemical corrosion resistance to common acid and alkali environments, ensuring that the electromagnetic shielding performance of the film is not affected under different environments. It has high stability. After extreme low temperature storage and high temperature heating treatment, the stability rate of electromagnetic shielding performance remains above 90%, and the stability after acid and alkali treatment remains above 95%;
[0011] Traditional uniform conductive systems produce strong reflections on incident electromagnetic waves, leading to secondary pollution. However, asymmetric electromagnetic shielding nanofiber films have unique structural advantages. The fibers form a continuous conductive network, which helps conduction losses, and the hierarchical porous interface structure is conducive to multiple reflections and absorption of electromagnetic waves.
[0012] Furthermore, in step (1), the SiO2 nanoparticles are generated by reacting tetraethyl silicate through a sol-gel method;
[0013] SiO2 nanoparticles prepared using the sol-gel method usually have good dispersibility and stability and are not easy to agglomerate, which is not only conducive to the subsequent preparation of the spinning solution, but also ensures the uniform distribution of the nanoparticles in the entire system, thereby improving the overall performance of the material. The sol-gel method is usually carried out under relatively mild conditions and does not require extremely high temperature or high pressure, reducing the impact on the environment.
[0014] Furthermore, the volume ratio of tetraethyl silicate, ammonia water, deionized water, and ethanol required for the sol-gel method is 3:4:15:55;
[0015] More specifically, the sol-gel process comprises the following steps:
[0016] In a fume hood, 3 mL of tetraethyl orthosilicate was added to a mixed solution of 55 mL of anhydrous ethanol and 15 mL of deionized water, and the mixture was stirred rapidly. Adding tetraethyl orthosilicate to the mixed solution of anhydrous ethanol and deionized water under rapid stirring can promote its uniform dispersion and avoid agglomeration caused by excessive local concentration, which is conducive to the generation of nanoparticles with uniform size distribution and regular morphology.
[0017] Then, 4 mL of ammonia water was added and stirring was continued for 5 h. Adding ammonia water as a catalyst can effectively adjust the pH value of the solution, accelerate the hydrolysis and condensation reaction of tetraethyl silicate, and maintain an appropriate reaction rate to prevent the formation of an uneven structure due to excessive or slow reaction. The 5-hour stirring ensured that the reaction was fully carried out and improved the yield.
[0018] The mixture was centrifuged at 7000 r / min for 5 min for washing and separation. The washing and centrifugation were repeated 5-6 times until the pH value of the supernatant was close to neutral (pH = 7). The unreacted raw materials and other impurities were completely removed by centrifugal washing and separation. This process not only improved the purity of the nanoparticles, but also reduced the risk of contamination in subsequent processing steps.
[0019] Finally, the white precipitate was freeze-dried for 12 hours to obtain SiO2 nanoparticles; freeze-drying is a mild and effective drying method that can remove moisture without destroying the structure of the nanoparticles to obtain dry powdered SiO2 nanoparticles with stable morphology and good dispersion;
[0020] SiO2 nanoparticles were prepared by sol-gel method using tetraethyl silicate (TEOS), ammonia, deionized water and ethanol in a volume ratio of 3:4:15:55. The overall benefit of this specific ratio is that it optimizes the entire reaction system and ensures efficient, stable and high-quality nanoparticle generation. This ratio not only promotes uniform dispersion and stable nanostructure formation, but also improves yield and purity.
[0021] The reaction conditions at this ratio can ensure sufficient hydrolysis and condensation while avoiding too fast or uncontrolled reactions, thereby preventing agglomeration and ensuring uniform size distribution of nanoparticles. A large amount of ethanol dilutes the system and reduces viscosity, which helps to evenly mix the components while inhibiting rapid polymerization. An appropriate amount of ammonia water acts as a catalyst to adjust the pH value, accelerate the reaction without causing drastic changes, and make the reaction rate moderate and controllable.
[0022] Furthermore, in step (2), the organic solvent is N,N-dimethylformamide (DMF), and the amount of SiO2 nanoparticles added is 5% by weight of the organic solvent;
[0023] N,N-dimethylformamide is a polar aprotic solvent with excellent solubility. It can effectively dissolve a variety of high molecular polymers and inorganic nanoparticles. It helps to ensure the uniform dispersion of SiO2 nanoparticles in the solution and prevent agglomeration, thereby improving the performance consistency of the final material. At the same time, N,N-dimethylformamide also has high chemical and thermal stability and can remain stable in a wide temperature range, which is beneficial to subsequent spinning and other high-temperature treatment processes. Its stability reduces the occurrence of side reactions and ensures the controllability and repeatability of the process.
[0024] An addition of 5% can provide sufficient filling density to enhance the mechanical strength and electromagnetic shielding performance of the material while ensuring that the nanoparticles are fully dispersed. Too many nanoparticles may cause agglomeration and affect the uniformity of the material, while too few are not enough to significantly improve the performance. The viscosity of the spinning solution at this ratio is moderate, which not only ensures the fluidity of the solution and facilitates the electrospinning operation, but is not too thin to form a stable fiber structure.
[0025] Furthermore, in step (2), the high molecular weight polymer is PAN (polyacrylonitrile);
[0026] PAN is a polymer material with excellent thermal stability, which is not easy to decompose or deteriorate under high temperature conditions; this makes it very suitable for subsequent high-temperature pre-oxidation and carbonization treatment, ensuring the stability of the material structure and the consistency of performance;
[0027] At the same time, PAN has excellent spinnability and can form slender and uniform nanofibers through electrospinning technology. This fiber-forming property is crucial for constructing electromagnetic shielding materials with high specific surface area and porous structure, which helps to improve the absorption and scattering effect of electromagnetic waves.
[0028] After high-temperature pre-oxidation and carbonization treatment, PAN can be converted into a stable carbon-based material. This conversion not only retains the morphology of the original nanofibers, but also gives the material excellent conductivity and mechanical strength, providing an ideal carbon source for the final generation of C / SiC composite membranes.
[0029] PAN and SiO2 nanoparticles have good compatibility and can coexist in the solution without agglomeration. This compatibility ensures the uniform dispersion of the two in the spinning solution and promotes the uniform formation of silicon carbide (SiC) in the subsequent reaction.
[0030] The method for uniformly stirring the spinning solution in step (2) is as follows: after adding PAN to the SiO2 nanoparticle dispersion, stirring and dissolving it at 60°C for 6-10 hours;
[0031] More specifically, the stirring is carried out in an oil bath pot, and the stirring and dissolving is carried out in the oil bath pot at 60° C. for 6-10 hours, which ensures that PAN is fully dissolved and uniformly mixed with SiO2 nanoparticles; mild heating conditions help to accelerate the dissolution process while avoiding damage to the material caused by excessively high temperatures;
[0032] In step (2), the spinning solution comprises: PAN with a mass fraction of 10% to 13% and SiO2 nanoparticles with a mass fraction of 5%;
[0033] PAN mass fraction is 10%-13%: PAN content within this range can ensure that the spinning solution has appropriate viscosity and fluidity, while not making spinning difficult due to too high a concentration or affecting the quality of fiber formation due to too low a concentration;
[0034] The mass fraction of SiO2 nanoparticles is 5%: the addition of an appropriate amount of SiO2 nanoparticles not only improves the mechanical strength and electromagnetic shielding performance of the material, but also optimizes the functional properties of the material without significantly increasing the cost.
[0035] Furthermore, the electrospinning parameters in (3) are:
[0036] The voltage is 15kV-17kV, the receiving distance is 10-15cm, the injection speed is 10μL / min-14μL / min, the spinning time is 12h-24h, the speed of the collecting device drum is 300-500rpm, and after the spinning is completed, the PAN / SiO2 nanofiber film is placed in a 60℃ oven for drying for 6-12h;
[0037] The voltage is 15kV-17kV. This voltage range provides sufficient electric field strength to overcome surface tension, allowing the solution to stably form a Taylor cone and eject slender fibers. At the same time, it avoids unstable ejection or excessive bead structure formation that may be caused by excessively high voltage, ensuring the quality and uniformity of the fibers.
[0038] The receiving distance is 10-15cm. This distance range ensures that the fiber has enough flight time to stretch and solidify, but does not cause excessive fiber dispersion due to the long distance, which affects the collection efficiency. A moderate receiving distance helps to obtain a nanofiber film with consistent morphology and orderly arrangement.
[0039] The injection speed directly affects the supply of spinning solution and the fiber diameter. The injection speed within 10μL / min-14μL / min can ensure continuous feeding while avoiding coarse fibers or breakage caused by excessive flow, thus ensuring the fineness and uniformity of the fibers.
[0040] The spinning time is 12h-24h. A longer spinning process can accumulate sufficient fiber layer thickness, thereby improving the mechanical strength and electromagnetic shielding performance of the final film. At the same time, long spinning time helps to achieve more uniform fiber distribution and reduce defects and gaps.
[0041] The rotating motion of the drum helps to spread the fibers evenly and avoid local accumulation or uneven distribution. The speed of the drum of the collecting device is set to 300-500rpm, which can ensure the effective deposition of the fibers and prevent the fibers from breaking or deforming due to excessive speed.
[0042] The drying process removes residual solvents, further enhances the cross-linking between fibers, and improves the overall stability and mechanical properties of the material. Drying at 60°C for 6-12 hours ensures that the fiber structure is not damaged and promotes uniform curing of the material.
[0043] By selecting and optimizing the electrospinning parameters and combining it with subsequent drying treatment, the quality and performance of the PAN / SiO2 nanofiber film were improved overall, ensuring an efficient, stable and economical production process, laying a solid foundation for the development of high-performance asymmetric electromagnetic shielding materials.
[0044] Furthermore, in step (4), the pre-oxidation is carried out in air at 200-250° C. for 120-150 min;
[0045] Pre-oxidation treatment can gradually transform the cyano groups in the PAN molecular chain into a cyclic structure with better heat resistance (such as ladder polymer), thereby improving the thermal and chemical stability of the material;
[0046] The pre-oxidation stage provides the necessary structural transformation foundation for the subsequent high-temperature carbonization; by initially removing some volatile components and forming stable intermediates, the carbonization process is made more efficient and stable, reducing the decomposition or weight loss that may occur during the carbonization process;
[0047] The temperature range of 200-250℃ is high enough to start the conversion reaction of PAN molecular chain, but not too high to cause rapid decomposition or excessive cross-linking of the material. It ensures the effective pre-oxidation process while maximally retaining the processability and functionality of the material.
[0048] The pre-oxidation time is 120-150 minutes. During this period, the PAN molecular chain has enough time to complete the transformation from linear to ladder structure and form a stable intermediate. The longer time also helps to uniformly heat and fully react, reducing the risk of local overheating or incomplete conversion.
[0049] Pre-oxidation is carried out in air. The presence of oxygen promotes the oxidative cross-linking of PAN molecular chains, further enhancing the thermal stability and mechanical properties of the material. In addition, air, as a common oxidizing medium, is simple to operate and low in cost, making it suitable for large-scale production.
[0050] Furthermore, the following treatment is performed before pre-oxidation in step (4):
[0051] The PAN / SiO2 nanofiber film was cut into appropriate sizes and placed on a ceramic sheet in the central area of the box furnace;
[0052] Cutting to a consistent size ensures that the sample is heated more evenly in the box furnace. Samples of different sizes may cause uneven heating and affect the pre-oxidation effect. Standardized sizes help reduce this difference and ensure that all samples can achieve the ideal pre-oxidation state;
[0053] The ceramic sheet has good high temperature resistance and chemical stability, can maintain structural integrity in high temperature environments, will not react with the sample or release harmful substances, and provides a stable support platform for the nanofiber film to prevent the sample from deforming or sticking to the inner wall of the furnace during heating;
[0054] The central area of the box furnace is usually where the temperature is most uniform, which can avoid temperature inconsistencies caused by edge effects. This ensures that the entire sample can be heated evenly, reduces the risk of local overheating or insufficient heating, and improves the effect and consistency of the pre-oxidation treatment.
[0055] Furthermore, in step (5), the method of using the Joule heat effect to cause a carbothermal reaction between SiO2 and the carbon-based film comprises:
[0056] Under the protection of argon, the Joule heating equipment adopts program-controlled mode to control the current and voltage to make the temperature reach 1700-1800℃ within 10s, and keep the temperature for 10s to form an asymmetric electromagnetic shielding nanofiber film with an asymmetric interface structure;
[0057] Carrying out the reaction under the protection of argon can effectively prevent oxygen and other impurities from entering the reaction system, avoiding unnecessary oxidation reactions or other side reactions, which helps to maintain the purity and performance stability of the material. The temperature is quickly raised to 1700-1800℃ within 10 seconds. The high temperature of 1700-1800℃ provides sufficient energy for the carbon thermal reaction between SiO2 and carbon-based materials, accelerates the formation of SiC, and also keeps the heat in a short time. This rapid heat treatment method can effectively activate the carbon thermal reaction, while avoiding the excessive impact of long-term high temperature on the material structure and reducing the generation of by-products.
[0058] The application method of the asymmetric electromagnetic shielding nanofiber film of the present invention, the asymmetric electromagnetic shielding nanofiber film is used as an electromagnetic shielding material, and the prepared asymmetric electromagnetic shielding nanofiber film optimizes the electromagnetic wave attenuation path through the conductive-dielectric gradient layer, improves the electromagnetic shielding performance, and exhibits excellent resistance to extreme temperatures and acid and alkali.
[0059] The asymmetric electromagnetic shielding nanofiber film prepared by the present invention was placed in a solution environment with different temperatures and pH values to test the electromagnetic shielding performance:
[0060] Among them, the temperature is divided into: low temperature (liquid nitrogen and refrigerator treatment), normal temperature (room temperature 25°C) and high temperature (100°C, 300°C and 500°C);
[0061] pH is divided into: 3, 5, 9 and 11.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] (1) The Fick diffusion effect is utilized to realize the concentration gradient migration of SiO2 vapor under high temperature conditions. The content of SiC nanoparticles on the surface of the film is induced to change layer by layer through heat treatment, forming a multilayer interface structure with conductive-dielectric gradient. In addition, the conductive-dielectric gradient in the film optimizes the impedance matching of electromagnetic wave attenuation, which can achieve efficient electromagnetic interference shielding.
[0064] (2) The prepared asymmetric membrane has unique structural advantages. The fibers form a continuous conductive network that helps conduction losses, and the hierarchical porous interface structure is conducive to multiple reflections and absorption of electromagnetic waves.
[0065] (3) The structure and performance of the asymmetric electromagnetic shielding nanofiber film after Joule heat treatment are stable at higher temperatures. At the same time, it has good resistance to chemical corrosion in common acid and alkali environments, ensuring that the electromagnetic shielding performance of the film is not affected in different environments. It has high stability. After extreme low temperature storage and high temperature heating treatment, the stability rate of electromagnetic shielding performance remains above 90%, and the stability after acid and alkali treatment remains above 95%.
[0066] (4) The present invention utilizes Joule heat to quickly initiate a reaction in a short time, causing silicon dioxide and the surface of the carbon-based film to rapidly undergo a carbon thermal reaction to generate SiC, significantly shortening the production cycle, improving production efficiency, and saving a lot of time and cost, which is in sharp contrast to the traditional long-term high-temperature treatment method;
[0067] (5) Through electrospinning, the mixing ratio of the solution, injection speed and other parameters can be precisely controlled, thereby accurately adjusting the ratio and distribution of components such as PAN and SiO2 in the nanofiber membrane, thereby affecting the electromagnetic shielding performance of the material. For example, by adjusting the spinning time to change the film thickness, precise regulation of the electromagnetic shielding performance can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0068] Figure 1 This is a SEM photo of the PAN / SiO2 nanofiber film prepared by electrospinning in Example 3;
[0069] Figure 2 The SEM image of the asymmetric C / SiC nanofiber film of Example 3, wherein a is the bottom, b is the middle, c is the top, and d is the XRD image;
[0070] Figure 3 The SEM image of the C / SiC nanofiber film with uniform structure prepared in a comparative tube furnace, where a is the bottom, b is the middle, c is the top, and d is the XRD image;
[0071] Figure 4 Figures a and b are comparison diagrams of the electromagnetic shielding performance of a C / SiC nanofiber film with a uniform structure prepared using a tubular furnace in the comparative example and an asymmetric C / SiC nanofiber film prepared in Example 3;
[0072] Figure 5 It is a comparison diagram of the electromagnetic shielding performance of Examples 1, 2, and 3;
[0073] Figure 6 This is a performance diagram of the asymmetric C / SiC film of Example 3 after being treated at different temperatures and acids and bases. DETAILED DESCRIPTION
[0074] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.
[0075] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0076] Secondly, the term "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0077] Embodiment 1:
[0078] A method for preparing an asymmetric electromagnetic shielding nanofiber film comprises the following steps:
[0079] (1) 3 mL of tetraethyl orthosilicate was dropped into a mixed solution of 55 mL of anhydrous ethanol and 15 mL of deionized water, and the mixture was stirred rapidly. Then, 4 mL of ammonia water was added and the stirring was continued for 5 h. The cleaning and centrifugal separation conditions were 7000 r / min and maintained for 5 min. The cleaning and centrifugation were repeated 6 times until the supernatant was neutral (pH = 7). The white precipitate was freeze-dried for 12 h to obtain SiO2 nanoparticles.
[0080] (2) 0.5 g SiO2 nanoparticles were dissolved in 10 mL DMF solution and stirred under ultrasound for 1 hour. Then 1 g PAN was added and stirred in an oil bath at 60 °C for 6 hours to obtain a uniform spinning solution. The spinning solution was carried out on an electrospinning machine with a high voltage of 17 kV and a flow rate of 14 μL / min. The distance between the needle and the collector was 15 cm. All experiments were carried out at room temperature with a humidity of about 50%. The speed of the collecting device drum was 500 rpm and the spinning time was 6 hours. After the spinning was completed, the PAN / SiO2 nanofiber film was placed in a 60 °C oven for drying for 12 hours.
[0081] (3) The PAN / SiO2 nanofiber film was cut into 10 cm × 10 cm squares and placed on a ceramic sheet in the central area of the furnace. The precursor was heated to 250 °C in air at a heating rate of 5 °C / min and kept at this temperature for 2 h. After pre-oxidation, it was cut into 3 cm × 1.5 cm rectangles.
[0082] (4) The Joule heating device is programmed in two stages. In the first stage, the current is set to 380A and the heating time is 10s. In the second stage, the current is set to 360A and the insulation time is 10s. Finally, it is naturally cooled to room temperature, and the asymmetric electromagnetic shielding nanofiber film of the present invention is successfully prepared.
[0083] Embodiment 2:
[0084] (1) The preparation of SiO2 nanoparticles and spinning solution is the same as in Example 1;
[0085] (2) The spinning time was increased to 12 h, and other electrospinning parameters were the same as those in Example 1;
[0086] (3) Pre-oxidation and Joule heat treatment are the same as in Example 1.
[0087] Embodiment 3:
[0088] (1) The preparation of SiO2 nanoparticles and spinning solution is the same as in Example 1;
[0089] (2) The spinning time was increased to 24 h, and other electrospinning parameters were the same as those in Example 1;
[0090] (3) Pre-oxidation and Joule heat treatment are the same as in Example 1.
[0091] Comparative Example:
[0092] This comparative example is a uniform electromagnetic shielding nanofiber film prepared by a traditional tubular furnace.
[0093] (1) The preparation of SiO2 nanoparticles and spinning solution is the same as in Example 1;
[0094] (2) A 3 cm × 1.5 cm pre-oxidized film was placed in a tubular furnace, heated to 1500 °C at a rate of 4 °C / min in argon, kept at this temperature for 2 h, and naturally cooled to room temperature to obtain a C / SiC nanofiber film with a uniform structure.
[0095] The asymmetric electromagnetic shielding nanofiber films prepared in Examples 1-3 and the uniform electromagnetic shielding nanofiber films prepared in the comparative example were placed in solution environments with different temperatures and pH values to test their electromagnetic shielding properties:
[0096] Among them, the temperature is divided into: low temperature (liquid nitrogen and refrigerator treatment), normal temperature (room temperature 25°C) and high temperature (100°C, 300°C and 500°C);
[0097] pH is divided into: 3, 5, 9 and 11.
[0098] Depend on Figure 1 It is known that PAN / SiO2 nanofiber film can be well prepared by electrospinning. PAN nanofibers present an interwoven three-dimensional porous structure, the fiber surface is relatively smooth, and a large number of SiO2 nanoparticles are attached to the fiber surface. These particles are evenly distributed and spherical. SiO2 nanoparticles are embedded in the fiber surface, showing a strong bond between the particles and the substrate.
[0099] Depend on Figure 2 Learn that Figure 2 The SEM images of ac in the figure show the C / SiC nanofiber film prepared using Joule heat. The asymmetric electromagnetic shielding nanofiber film is divided into three parts: top, middle and top; a is the bottom, b is the middle, and c is the top. A large number of holes are generated on the surface of the carbon nanofiber, and SiC nanoparticles with different contents are loaded on the surface of different layers, indicating that the gradient distribution of SiC content will be significantly affected by Joule heat. At high temperatures, SiO2 will gasify. Combined with Fick's diffusion theory, its vapor can migrate from the bottom of the film to the top of the film under the action of high temperature and pressure, and the probability of SiC formation gradually increases, leading to an asymmetric structure. Figure d shows X-ray diffraction (XRD), which is used to reveal the detailed crystal structure of the synthesized C / SiC film. All characteristic peaks can be indexed as PDF#29-1129 and PDF#41-1487, which means that a mixed phase of β-SiC and graphitic carbon with good crystal properties is formed. The diffraction peaks at 35.5°, 41.0°, 59.9° and 71.7° can be well calibrated to the crystal planes (111), (200), (220) and (311), respectively. The peak at 2θ=33.6° corresponds to the stacking stagger (SF) in the (111) plane of SiC. The increase in layer dislocation density is conducive to the promotion of dipole polarization.
[0100] Depend on Figure 3 Learn that Figure 3 The SEM images in the middle ac show the C / SiC nanofiber film prepared using the traditional method of tube furnace. Some holes appear on the surface of the carbon nanofiber, but some balls are still intact. The morphology of each layer is similar. Figure 3 As can be seen in Figure d, the diffraction peak further confirms the uniform distribution of SiC in the tubular furnace heating film.
[0101] Depend on Figure 4 Learn that Figure 4 Figure a shows a comparison of the shielding performance of a C / SiC nanofiber film with a uniform structure prepared using a tube furnace and an asymmetric electromagnetic shielding nanofiber film prepared using Joule heat. The electromagnetic shielding performance in the X-band (8-12GHz) remains at 17dB. In contrast, when using the rapid Joule heat method, the electromagnetic shielding performance of the conductive gradient structure reaches 47dB. Figure 4As shown in (b), the electromagnetic shielding parameters are the total shielding effect (SET), shielding reflection loss (SER) and shielding absorption loss (SEA); compared with the tube furnace method (SER = 2.8 dB), the SER (13.7 dB) of Joule heat is higher; in addition, the SEA (33.7 dB) of the asymmetric structure C / SiC nanofiber film obtained by Joule heat treatment is attributed to the absorption-reflection-absorption interface in the gradient conductive structure framework. This high absorption is due to the impedance matching in the interface between the top layer and the transition layer. Therefore, a reasonable gradient distribution of the top (impedance matching) and bottom (impedance mismatching) layers is beneficial for achieving efficient absorption and reflection.
[0102] Depend on Figure 5 It is known that the electromagnetic shielding performance of the asymmetric electromagnetic shielding nanofiber film increases with the thickness of the film. As the thickness of the film increases, the path of electromagnetic waves propagating inside the material becomes longer, and the material has more opportunities to absorb and reflect electromagnetic waves. At the same time, the increase in thickness means that there are more absorption media interacting with electromagnetic waves, thereby improving the absorption efficiency. This also reflects that the adjustment of the spinning time parameters in the electrospinning process can accurately control the electromagnetic shielding performance.
[0103] Depend on Figure 6 It is known that the asymmetric electromagnetic shielding nanofiber film has excellent high temperature resistance and acid and alkali resistance. After extreme low temperature storage and high temperature heating treatment, the stability rate of electromagnetic shielding performance remains above 90%; after low temperature treatment, the electron transmission rate decreases and the electrical conductivity decreases, resulting in a decrease in the number of reflected and absorbed electromagnetic waves; after high temperature treatment, the electron transmission rate inside the material increases and the electrical conductivity increases, enhancing the electromagnetic wave shielding performance. In addition, the material still maintains stable performance after acid and alkali treatment, and the stability remains above 95%, which is attributed to the stability of SiC and its non-reaction with acids and alkalis, which provides important protection for the stability of performance.
[0104] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an asymmetric electromagnetic shielding nanofiber film, characterized in that: The following steps are involved: (1) preparing SiO2 nanoparticles as a silicon source; (2) dissolving SiO2 nanoparticles in an organic solvent, stirring and ultrasonicating the solvent to obtain a SiO2 nanoparticle dispersion; then adding a high molecular weight polymer as a carbon source to the SiO2 nanoparticle dispersion, and uniformly stirring the solvent to obtain a spinning solution; (3) transferring the spinning solution into a syringe, adjusting the electrospinning parameters and performing electrospinning on the spinning solution to prepare a PAN / SiO2 nanofiber film; (4) pre-oxidizing the PAN / SiO2 nanofiber film to carbonize the polymer to form a carbon-based skeleton, thereby obtaining a carbon-based film; (5) Using the Joule heating effect, SiO2 and carbon-based films undergo a carbon thermal reaction to generate silicon carbide, and an asymmetric interface structure is constructed to obtain an asymmetric electromagnetic shielding nanofiber film.
2. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 1, characterized in that: In the step (1), the SiO2 nanoparticles are generated by reacting tetraethyl silicate through a sol-gel method.
3. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 2, characterized in that: The volume ratio of tetraethyl silicate, ammonia water, deionized water and ethanol required for the sol-gel method is 3:4:15:
55.
4. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 1, characterized in that: In the step (2), the organic solvent is N,N-dimethylformamide, and the amount of SiO2 nanoparticles added is 5% of the weight of the organic solvent.
5. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 4, characterized in that: In the step (2), the high molecular weight polymer is PAN; The method for uniformly stirring the spinning solution in step (2) is as follows: after adding PAN to the SiO2 nanoparticle dispersion, stirring and dissolving it at 60°C for 6-10 hours; In the step (2), the spinning solution comprises: PAN with a mass fraction of 10%-13%, and SiO2 nanoparticles with a mass fraction of 5%.
6. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 1, characterized in that: The electrospinning parameters in (3) are: The voltage is 15kV-17kV, the receiving distance is 10-15cm, the injection speed is 10μL / min-14μL / min, the spinning time is 12h-24h, the speed of the collecting device drum is 300-500rpm, and after spinning, the PAN / SiO2 nanofiber film is placed in a 60℃ oven for drying for 6-12h.
7. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 1, characterized in that: The pre-oxidation in step (4) is carried out in air at 200-250° C. for 120-150 minutes.
8. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 7, characterized in that: The following treatment is performed before pre-oxidation in step (4): The PAN / SiO2 nanofiber film was cut into suitable sizes and placed on a ceramic sheet in the central area of the box furnace.
9. The method for preparing the asymmetric electromagnetic shielding nanofiber film according to claim 1, characterized in that: The method of utilizing the Joule heat effect in step (5) to cause a carbon thermal reaction between SiO2 and the carbon-based film comprises: The process is carried out under argon protection, and the Joule heating equipment adopts a program-controlled mode to control the current and voltage so that the temperature reaches 1700-1800°C within 10 seconds and is kept warm for 10 seconds to form an asymmetric electromagnetic shielding nanofiber film with an asymmetric interface structure.
10. A method for applying the asymmetric electromagnetic shielding nanofiber film prepared by the method for preparing the asymmetric electromagnetic shielding nanofiber film according to any one of claims 1 to 9, characterized in that: The asymmetric electromagnetic shielding nanofiber film is used as an electromagnetic shielding material.
Citation Information
Patent Citations
Low-density SiC nanofibers and preparation method thereof
CN104451957A
A method for preparing a carbon-based electrocatalyst based on Joule pyrolysis
CN108963280A
Preparation method of silicon carbide nanowires
CN109763203A
Preparation method of Si / SiC / C nanofiber membrane, battery negative electrode and lithium ion battery
CN113097469A
Method for preparing surface-modified electromagnetic shielding material through Joule heat treatment
CN115160866A
Cited By
High-durability micro-nano structure carbon-ceramic composite material brake disc and preparation method thereof
CN120736915A